Collaborative Participation Management within the Ecology of Faith-Based Organizations: Students’ Engagement in the Islamic Religious Education Tutorial Program - Yusep Budiansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to explore the perspectives of university students who serve as administrators in the Islamic Religious Education (PAI) Tutorial Program and their collaborative experiences within the organization managed by PAI lecturers. The analysis is framed through three organizational dimensions: institutional, interpersonal, and individual. Employing a qualitative approach with a phenomenological design, the study involved five PAI lecturers and 78 student participants who shared their views and lived experiences. Data were analyzed using procedures of reduction, display, and conclusion drawing. This study found: First, from the institutional dimension, the PAI Tutorial Program originated as a cultural-ecological initiative and evolved into a formal academic entity recognized by the university. The substantial number of participants necessitated student recruitment into various administrative divisions, including participant affairs, human resources, media and communication, research and development, and monitoring and evaluation. The organizational culture, which upholds Islamic values, operates dynamically and flexibly, promotes egalitarianism, eschews seniority, and embraces gender equity, all of which motivated students to become actively involved. Second, in terms of the interpersonal dimension, the program fosters peer-based interaction and inter-organizational partnerships, positioning itself as a relational space that is both transformative and socially supportive of students' psychosocial development. Third, at the individual level, the study identified four primary motivations for student involvement: religious commitment, social-relational aspirations, personal growth, and constructive time engagement. Additionally, extrinsic motivations, such as influence from peers, family, seniors, alumni, and the organization’s inclusive and syar’i culture, played a stronger role than intrinsic motives, which include the desire for self-improvement and spiritual proximity. This study advances the development of progressive and transformative religious organizational ecosystems in public universities, directly contributing to the attainment of SDG targets in quality education, social inclusion, and psychosocial well-being